RNA structure-function analysis of regulatory regions of p53 mRNA - Pereira, Bruna F. (2019)
At least half of all tumors exhibit mutations in the tumor suppressor p53 gene. Indeed, the fact that p53 is frequently mutated in cancer led to its identification as an oncogene, when first described in 1979. Later, it was classified as a tumor suppressor, due to the clarification of its wild-type role in maintaining genome integrity and preventing malignant transformation. The p53 gene can encode for many p53 isoforms, by alternative splicing, alternative promoters and internal translation initiation mechanisms. While full-length p53 (FL-p53) protein works as a tumor suppressor by regulating many biological processes such as cell cycle, apoptosis, senescence and DNA repair, shorter p53 protein isoforms seem to play different roles in the cell. Recently, we have shown that the most common p53 mutations induce the expression of shorter p53 isoforms. Furthermore, we found that shorter p53 isoforms are implicated in cancer progression as they promote enhanced cell survival, proliferation, adhesion and formation of invasive cell structures. Here, with a bicistronic system containing two reporter genes (Renilla luciferase and firefly luciferase), we show that expression of shorter p53 isoforms is mediated by a non-canonical translation initiation mechanism regulated by an Internal Ribosome Entry Site (IRES) in the p53 mRNA. By investigating the effect of common p53 missense mutations on the function of this new IRES, through bioluminescence assays and Western blot analysis, we show that some p53 cancer mutations have a preponderant role in IRES-mediated translation induction of shorter p53 isoforms. With the obtained results we identified a new mechanism by which p53 cancer mutations promote tumorigenesis, which may lead to new understandings of the onset and progression of some types of tumors as well as to the development of new cancer therapies.